SERVICE QUALITY, PRICING, AND CUSTOMER SATISFACTION EFFECTS ON REFERRAL INTENTION: A CASE STUDY OF JAJAN DOELOE CAFÉ - Pakpahan, Arnoldus; Onaning, Kamaruzzaman (jfpublisher, 2025)
The rapid expansion of café businesses in Indonesia reflects changing consumer lifestyles characterized by increased social dining and leisure activities. However, intensified competition has created challenges for establishments that fail to prioritize customer-centric approaches, potentially leading to customer defection and reduced referral behaviors. This study investigates the determinants of referral intention in the café industry, specifically examining how service quality, pricing, and customer satisfaction influence customers' willingness to recommend establishments to others. The research employed a quantitative methodology utilizing survey data from 100 customers of Jajan Doeloe Café in Bogor, Indonesia. Data analysis was conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3.0 to test the proposed hypotheses. The measurement instruments incorporated established scales including SERVQUAL dimensions for service quality assessment and validated constructs for pricing perception, customer satisfaction, and referral intention. The empirical findings reveal significant variations in the influence of different factors on referral intention. Customer satisfaction emerged as the strongest predictor of referral behavior (β=0.526, p<0.001), followed by pricing perceptions (β=0.276, p=0.002). Surprisingly, service quality demonstrated no significant impact on referral intention (β=0.005, p=0.937). These results suggest that in the café context, customer satisfaction and perceived value through appropriate pricing strategies are more critical for generating positive word-of-mouth recommendations than traditional service quality dimensions. The findings provide strategic guidance for café management prioritization and resource allocation decisions.